Relation of alpha-1-antitrypsin phenotype to the performance of pulmonary function tests and to the prevalence of respiratory illness in a working population. Issue 2 (April 1976) - Cole, R B; Nevin, N C; Blundell, G; Merrett, J D; McDonald, J R; Johnston, W P
Abstract : Individuals with severe alpha-1-antitrypsin (alpha1AT) deficiency (phenotype Pi ZZ) are abnormally liable to develop emphysema, but it is uncertain whether those with partial alpha1AT deficiency (phenotypes Pi MS and MZ) are similarly susceptible. This study was undertaken to determine the frequency of the various Pi phenotypes in a working population in Northern Ireland and to compare the performance of simple pulmonary function tests and prevalence of respiratory symptoms and chest illness between different phenotypes. The population sample consisted of 1995 working men and women aged between 35 and 70 years. The MRC Questionnaire (1966) was used to assess respiratory symptoms, a forced expiratory spirogram was recorded, and a blood sample was analysed for alpha1AT phenotype by acid starch gel electrophoresis and antigen-antibody crossed electrophoresis in every case. The percentage frequencies of the alpha1AT phenotypes were: Pi MM 86-5; MS 7-97; MZ 3-86; IM 0-6; FM 0-4; SZ 0-25; M 0-15; SS 0-1; Z 0-05; MP 0-05; FS 0-05. Respiratory symptoms and a history of previous chest illness occurred with similar frequency among the Pi M, MS, and MZ phenotypes, and a comparison of the regression coefficients for FEV1, FVC, and MMF on age for each phenotype group showed no significant differences between them overall, or when subdivided according to smoking habits or dust exposure. These findings provide no evidence that individuals of phenotype Pi MS or MZ are more than usually liable to develop chronic airways obstruction.